Cleaning symbiosis between wrasses (Labridae) and lice infested salmon (Salmo salar) in mariculture - Bjordal, Åsmund (ICES, 1988)
Epidemic infestation by the crustacean ectoparasitic salmon lice (Lepeophteirus salmonis) is a major problem in marine salmon farming. Cleaning symbiosis between different labrid species and lice infested salmon is described, and the possible application of this principle in full scale salmon farming is discussed.